Chapter 4 Elements of an Evolutionary Approach to Comparative Economic Studies - Gräbner-Radkowitsch, Claudius (Taylor & Francis, 2023)
This chapter delineates an evolutionary approach to the comparative analysis of economic systems and illustrates its usefulness via an exemplary application to recent developments in the European Union. The first part of the chapter describes the meta-theoretical foundations of the approach, i.e. its particular ontological and epistemological vantage points. This allows for an easier comparison (and, potentially, triangulation) with other approaches to comparative analyses, and already provides for some practical guidelines for applied work. The second part applies the approach and studies polarization patterns in the European Union. While this application is not meant as a fully self-contained analysis, it not only illustrates how the concepts of the approach can be operationalized and applied in practice, but also the application of several empirical methods that can be used fruitfully within such an evolutionary analysis. The chapter concludes with a non-exhaustive list of concepts and topics that are particularly insightful to consider when conducting an analysis in the spirit of an evolutionary approach to the comparative analysis of economic systems.